Mothers’ health care seeking behavior and associated factors for common childhood illnesses, Northwest Ethiopia: community based cross-sectional study - Muluye Molla Simieneh (BMC Health Services Research, 2019)
Abstract Background Substantial progress has been made in reducing child mortality over the last decades, however the magnitude of the problem is yet high globally Appropriate health care-seeking behavior of mothers/guardians for common childhood illnesses could prevent a significant number of child deaths and complications due to childhood illnesses, currently, there is few of studies in Ethiopia. Therefore, this study aimed to assess mothers/caregivers health care seeking behavior for their children in Northwest Ethiopia. Methods Community based cross-sectional study of rural mothers living in Aneded district from February to March 2016. Data were collected using structured questionnaire by an interviewer. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with health care seeking behavior. Variables having P value ≤0.2 in the bivariate analysis were considered for multivariable analysis. P-value less than 0.05 was used to declare that there was statistically significant association. Odds Ratio (OR) with 95% confidence interval (CI) was used to determine the strength and direction of association. Result A total of 410 mothers participated in this study. Among 48.8% (95% CI: 44, 53.6%) had sought health care, only 27% sought health care within a day. Having awareness of childhood illness (AOR = 3.8, 95% CI: 2.18–6.72), perceived importance of early treatment (AOR = 3.5, 95% CI: 2.00–6.07) and child age <  24 months (AOR = 1.7, 95% CI: 1.08–2.68) and illness not being perceived as severe (AOR:= 0.17, 95% CI: 0.09–0.30) were all factors associated with mothers healthcare seeking behavior during their child illness. Conclusion Overall health care seeking behavior level was low. Awareness, perceived illness severity, perceived early treatment and having young children were predictors of mothers’ health care seeking behavior. The Woreda health office administrators and health professionals should work to improve mothers’ awareness and perception towards childhood problems and the importance of early seeking appropriate health care using the existed structures (one-to-five women networking and health developmental army).